2016
DOI: 10.1002/jbm.a.35804
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐effect of nanoparticles in the cardiovascular system

Abstract: Nanoparticles (NPs; < 100 nm) are increasingly being applied in various fields due to their unique physicochemical properties. The increase in human exposure to NPs has raised concerns regarding their health and safety profiles. The potential correlation between NP exposure and several cardiovascular (CV) events has been demonstrated. The aim of this review is to provide a comprehensive evaluation of the current knowledge regarding the bio-toxic impacts of titanium oxide, silver, silica, carbon black, carbon n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 146 publications
(296 reference statements)
1
42
0
3
Order By: Relevance
“…4,5 Therefore, it is critical to find an effective and safe additive ingredient to develop novel fish collagen wound healing materials. It was reported that bioactive glass (BG) could be incorporated into the polymer matrix, and this was found to enhance the mechanical and biological properties of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Therefore, it is critical to find an effective and safe additive ingredient to develop novel fish collagen wound healing materials. It was reported that bioactive glass (BG) could be incorporated into the polymer matrix, and this was found to enhance the mechanical and biological properties of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…Stres-strain eğrisinden maksimum stres, maksimum strain, dayanıklılık ve Young modülü hesaplanmıştır. 5 Birim alana etki eden maksimum kuvvet olarak tanımlanan maksimum stres (σ) maksimum kırılma kuvvetinin alan (A) değerine bölünmesiyle (σ=F max /A), maksimum strain (ε), maksimum deformasyon miktarının kemiğin kuvvet uygulanmadan önceki değerine bölünmesiyle (ε=∆L/L 1 ), dayanıklılık (D) stres-strain eğrisinin altında kalan alanın hesaplanmasıyla (D=(σ*ε)/2) ve Young modül (Y) ise stres/strain oranından hesap- …”
Section: Bi̇yomekani̇k Testunclassified
“…Bu parçacıklar başta tıp olmak üzere elektronik, otomotiv, tekstil, boya, kozmetik ve gıda alanlarında yaygın olarak kullanılmaktadır. 5 Nanoteknolojide sıklıkla gümüş, titanyum dioksit, çinko oksit, altın, silisyum dioksit gibi çeşitli metaller kullanılmakta-dır. Bunlardan gümüş; atık su ve kaynak su temizliği ile tekstil ve kozmetikte, farmakolojide; titanyum dioksit kozmetikte, gıda sektöründe, araç kaplamalarında, ilaç taşıyıcı sistemlerde, çinko oksit kozmetik, gıda paketleme ve araç kaplamada; altın ise özellikle tıpta kullanım alanı bulmaktadır.…”
unclassified
See 1 more Smart Citation
“…Many benefits are expected from their use but potential toxic effects related to NPs exposures have been highlighted [1][2][3][4]. Due to their small size NPs are able to enter into our body.…”
Section: Introductionmentioning
confidence: 99%